Exploitation of Heterosis for Yield and Quality Enhancement in Pumpkin (Cucurbita moschata Duch. Ex Poir.) Hybrids - Akshita Bisht; Suresh Kumar Maurya; Lalit Bhatt; Dhirendra Singh; Birendra Prasad; Sudhanshu Verma; Vinay Kumar; Pratapsingh S. Khapte; Nazim S. Gruda; Pradeep Kumar (Horticulturae)
The hybrid development of pumpkins, utilizing local genetic material, has recently garnered attention in India. This study aimed to evaluate the combining ability, heterosis, and per se performance of pumpkin hybrids for yield-related and biochemical traits. In the present investigation, eight parental lines of pumpkins were hybridized using a half-diallel mating design, resulting in 28 F1 hybrids (reciprocals not included). The produced F1 hybrids, parental lines, and a commercial check were assessed in a randomized complete block design with three replications during the summers of 2023 and 2024. The results obtained in the study show that the best performers with the most desirable characteristics were P-7 for total soluble solid, dry matter content, and average fruit weight; P-3 for total carotenoids, number of seeds per fruit, and antioxidant activity; P-2 for yield per plant and flesh thickness; and P-8 for number of fruits per plant. The parent P-5 for fruit number, average fruit weight, and yield per plant; P-2 for flesh thickness and antioxidant activity; P-7 for TSS and dry matter content; P-1 for fruit number; and P-3 for total carotenoids were noted as the best general combiners in terms of the effects of the parental lines on general combining ability. Conversely, the crosses P-2 × P-5 for yield per plant and flesh thickness and P-1 × P-2 for DPPH activity were found to outperform better-parent heterosis and standard heterosis in terms of heterosis and the specific combining ability magnitude of the F1 hybrids. Thus, the findings of this study reveal that these hybrids possess strong potential for commercial cultivation, contributing to the development of high-yielding and nutritionally superior pumpkin hybrids after being tested in various seasons and locations.